The Ethical Mutual Fund Performance Debate: New Evidence from Canada - Bauer, Rob (Journal of business ethics, 2007)
Although the academic interest in ethical mutual fund performance has developed steadily, the evidence to date is mainly sample-specific. To tackle this critique, new research should extend to unexplored countries. Using this as a motivation, we examine the performance and risk sensitivities of Canadian ethical mutual funds vis-à-vis their conventional peers. In order to overcome the methodological deficiencies most prior papers suffered from, we use performance measurement approaches in the spirit of Carhart (1997, Journal of Finance 52(1): 57–82) and Ferson and Schadt (1996, Journal of Finance 51(2): 425–461). In doing so, we investigate the aggregated performance and investment style of ethical and conventional mutual funds and allow for time variation in the funds’ systematic risk. Our␣Canadian evidence supports the conjecture that any␣performance differential between ethical mutual funds and their conventional peers is statistically insignificant.